2020
DOI: 10.3389/fcell.2020.579919
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Roles of RNA N6-Methyladenosine in Urological Tumors

Abstract: N6-methyladenosine (m 6 A) is regarded as the most abundant, prevalent and conserved internal mRNA modification in mammalian cells. M 6 A can be catalyzed by m 6 A methyltransferases METTL3, METTL14 and WTAP (writers), reverted by demethylases ALKBH5 and FTO (erasers), and recognized by m 6 A-binding proteins such as YTHDF1/2/3, IGF2BP1/2/3 and HNRNPA2B1 (readers). Emerging evidence suggests that m 6 A modification is significant for regulating many biological and cellular processes and participates in the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 145 publications
(166 reference statements)
0
13
0
Order By: Relevance
“…We also explored the correlation between DNA alterations and the MCM complex, but we found that the frequency of DNA alterations was not high, and it was unlikely that DNA alterations led to dysregulation of the MCM complex. Non-coding RNA is a clear example of how inherited epigenetic changes can play a role in carcinogenesis, and non-coding RNA is the most abundant type of RNA ( 47 ). Therefore, we detected the potential regulatory association among miRNAs and the MCM complex.…”
Section: Discussionmentioning
confidence: 99%
“…We also explored the correlation between DNA alterations and the MCM complex, but we found that the frequency of DNA alterations was not high, and it was unlikely that DNA alterations led to dysregulation of the MCM complex. Non-coding RNA is a clear example of how inherited epigenetic changes can play a role in carcinogenesis, and non-coding RNA is the most abundant type of RNA ( 47 ). Therefore, we detected the potential regulatory association among miRNAs and the MCM complex.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 22 m6A regulators were collected from relevant studies ( Li et al, 2020a ; Yi et al, 2020 ; Zheng et al, 2021 ); the regulators included 7 “writers” (WTAP, METTL16, VIRMA, RBM15B, METTL3, RBM15, and ZC3H13), 13 “readers” (YTHDC1, YTHDF1, YTHDC2, YTHDF3, IGF2BP2, LRPPRC, YTHDF2, HNRNPA2B1, HNRNPC, RBMX, EIF3A, G3BP1 and FXR1), and 2 “erasers” (ALKBH5 and FTO). The prognostic role of the m6A regulators was assessed using the Kaplan-Meier (KM) diagrams and Cox proportional hazards model.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast with DNA modifications, which are known to mainly regulate gene expression [ 136 ], RNA modifications control many functions apart from transcription such as RNA stability, location, splicing, degradation or translation efficiency [ 134 , 137 , 138 ]. For instance, 5-methylcytosine (m 5 C) methylation of tRNAs stabilises their structure and protects them from nuclease-mediated cleavage [ 137 ].…”
Section: Epitranscriptomics Alterations In Prostate Cancermentioning
confidence: 99%